Optimation Model of Planning Investment Dockyard with Approach Multi Objective Goal Programming - Azhar, Ali (UI Scholars Hub, 2002)
Optimation model of planning investment dockyard with approach multi objective goal programming. The purpose of this research is to determine decision variable, goal function, alternative priority and achievement function in investment planning. From this optimation component, the model of ship yard investment planning could be achieved. The model of developed model in this research was the optimation of ship yard investment planning using multi objective goal programming approach. The model consist of 5 decision variable, 11 goal function, 2 alternative priority and 11 achievement functions. The model implementation was done toward PT ASSI investment planning. The calculation using from Quantitative System 3.0 was that the quantity of decision variable parameters could be achieved. The first alternative was based on the difference goal priority, and the second alternative based on similiar goal priority.